Baseline states of organic constituents in the Athabasca river system upstream of Fort McMurray - Peake, E.; Strosher, M. T. (1979)
Investigations were carried out on the Athabasca River upstream of Fort McMurray to determine the baseline quantities of organic constituents and their contribution to the organic water quality of the river system as it continues through the Athabasca Oil Sands strip mining area. Results of these investigations were evaluated to assess the fate of organic matter in this segment of the river. Studies focussed on the natural occurrence of classes of compounds which are known to be major constituents of wastewaters from oil sands processing. Major groups of naturally occurring organic compounds and a limited number of labile compounds were also considered as a means of assessing the assimilative capacities of this river segment. Water soluble constituents, tannins and lignins, asphaltenes, and polar constituents were the major organic components of the river system as determined from the 16 different investigations carried out. Water samples contained an average 9 mg/l of organic carbon, the majority of which was determined as dissolved organic carbon. Water soluble organics, which include the humic acids, averaged 6.9 mg/l and were the largest single organic component of the river water. Also contained in this water soluble fraction were the naturally occurring tannin and lignins at 0.24 mg/l. The extractable carbon fraction contained 20% asphaltenes, 33% polar constituents, and 10% hydrocarbons. Sediment samples contained an average 11,000 to 20,000 mg/kg of total organic carbon, 6% of which occurred as extractable organic carbon. Tannins and lignins were the largest group of compounds detected in the sediments but comprised only 3% of their unextractable carbon fraction. Extractable organic carbon fractions contained 39% asphaltenes, 17% polar compounds, and 16% hydrocarbons. On the basis of these investigations, it is concluded that organic constituents which occur in this segment of the river are mainly water soluble, naturally occurring compounds that persist consistently throughout this upstream study area. ...